Reputation without commitment in finitely-repeated games - Muhamet Yildiz; Jonathan Weinstein (Theoretical Economics, 2016)
In the reputation literature, players have commitment types which represent the possibility that they do not have standard payoffs but instead are constrained to follow a particular plan. In this paper, we show that arbitrary commitment types can emerge from incomplete information about the stage payoffs. In particular, any finitely repeated game with commitment types is strategically equivalent to a standard finitely repeated game with incomplete information about the stage payoffs. Then, classic reputation results can be achieved with uncertainty concerning only the stage payoffs.
Keywords: C72; C73; 330; Reputation; repeated games; commitment